4(2x+-1)=27+3(2x-5)

Simple and best practice solution for 4(2x+-1)=27+3(2x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+-1)=27+3(2x-5) equation:


Simplifying
4(2x + -1) = 27 + 3(2x + -5)

Reorder the terms:
4(-1 + 2x) = 27 + 3(2x + -5)
(-1 * 4 + 2x * 4) = 27 + 3(2x + -5)
(-4 + 8x) = 27 + 3(2x + -5)

Reorder the terms:
-4 + 8x = 27 + 3(-5 + 2x)
-4 + 8x = 27 + (-5 * 3 + 2x * 3)
-4 + 8x = 27 + (-15 + 6x)

Combine like terms: 27 + -15 = 12
-4 + 8x = 12 + 6x

Solving
-4 + 8x = 12 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-4 + 8x + -6x = 12 + 6x + -6x

Combine like terms: 8x + -6x = 2x
-4 + 2x = 12 + 6x + -6x

Combine like terms: 6x + -6x = 0
-4 + 2x = 12 + 0
-4 + 2x = 12

Add '4' to each side of the equation.
-4 + 4 + 2x = 12 + 4

Combine like terms: -4 + 4 = 0
0 + 2x = 12 + 4
2x = 12 + 4

Combine like terms: 12 + 4 = 16
2x = 16

Divide each side by '2'.
x = 8

Simplifying
x = 8

See similar equations:

| x(x+3)=18 | | 38=25+2y | | 7p=6p^2-3 | | v^2-6v+15= | | 0=-16t^2+35t+8 | | 1-5x^2=-3x | | 3(q+4)-10q=2q+3 | | 2x+3x+5=5(2x-3) | | 4z-2(z+6)=7z+8 | | 5x^2-30x-80= | | 6y+2y=9-3y | | 2x-5x=5+4y | | 5x-x+7x= | | 3x+2=5-x | | 2x=3x-2 | | 502.4=12(3.141592654)(r)+(3.141592654)(r^2) | | 4p^2q+q^3-q^2=0 | | 502.4=12(pi)(r)+(pi)(r^2) | | 4-2n=5n+n | | 33=P(0.06)3 | | 6+2n=4n-3n | | 8v+1=7v-2-0 | | 9-(4y-9)=8-5y | | -21c+19=21c-1 | | -36+3x^2=0 | | 3x^2*x=108 | | 18=15-n+3 | | 0.5(6x+12)=1.3-(x+2) | | 6x-y=17 | | 2-2n=n+15 | | -20=10-6+n | | -16=5+n |

Equations solver categories